Photochemical Study of Hydrated Ammonium Aluminum Sulfate-Urea Ionic Liquid by FT-IR Spectroscopy. - Akram, Evon (Al-Nahrain Journal of Science, 2018)
The stability of ionic liquid which makes it interest to study the photochemistry of hydrated ammonium aluminum sulfate NH4Al SO4)2.12H2O-urea CO NH2)2 sample to show photo degradation rate by FTIR spectra effect with different times which indicated a few influence irradiation the ionic liquid with increase time that indication stability of ionic liquids green chemistry).